Chemically Cross-Linked Cellulose Nanocrystal Aerogels for Effective Removal of Cation Dye - Liang, Luna; Zhang, Shuyang; Goenaga, Gabriel A.; Meng, Xianzhi; Zawodzinski, Thomas A.; Ragauskas, Arthur J. (Frontiers in Chemistry, 2020)
In this study, porous aerogels were prepared by directional freeze-drying via cross-linking cellulose nanocrystals (CNCs) with poly(methyl vinyl ether-co-maleic acid) (PMVEMA) and poly(ethylene glycol) (PEG). The thermal properties and physical adsorption performance toward cation methylene blue dye of the obtained CNC aerogels were investigated. The maximum degradation temperature was increased from 324 °C of CNCs to 355 °C of cross-linked CNC aerogels. The dye adsorption isotherm results showed that the maximum methylene blue adsorption capacity of CNC aerogels was 116.2 mg g-1, according to the Langmuir model, which was mainly due to the electrostatic attractions between negatively charged carboxyl groups or sulfonate groups on the CNC aerogles and cation MB molecules. The reusability test showed that the CNC aerogels contained the same dye adsorption performance in five adsorption/desorption cycles. Overall, this study described an ideal alternative for water purification with high dye adsorption capacity and enhanced physical performance.